Why is chlorophyll b only used in light-harvesting systems? - Kume, Atsushi; Akitsu, Tomoko; Nasahara, Kenlo Nishida (Journal of plant research, 2018)
Chlorophylls (Chl) are important pigments in plants that are used to absorb photons and release electrons. There are several types of Chls but terrestrial plants only possess two of these: Chls a and b . The two pigments form light-harvesting Chl a / b -binding protein complexes (LHC), which absorb most of the light. The peak wavelengths of the absorption spectra of Chls a and b differ by c. 20 nm, and the ratio between them (the a / b ratio) is an important determinant of the light absorption efficiency of photosynthesis (i.e., the antenna size). Here, we investigated why Chl b is used in LHCs rather than other light-absorbing pigments that can be used for photosynthesis by considering the solar radiation spectrum under field conditions. We found that direct and diffuse solar radiation (PAR dir and PAR diff , respectively) have different spectral distributions, showing maximum spectral photon flux densities (SPFD) at c. 680 and 460 nm, respectively, during the daytime. The spectral absorbance spectra of Chls a and b functioned complementary to each other, and the absorbance peaks of Chl b were nested within those of Chl a . The absorption peak in the short wavelength region of Chl b in the proteinaceous environment occurred at c. 460 nm, making it suitable for absorbing the PAR diff , but not suitable for avoiding the high spectral irradiance (SIR) waveband of PAR dir . In contrast, Chl a effectively avoided the high SPFD and/or high SIR waveband. The absorption spectra of photosynthetic complexes were negatively correlated with SPFD spectra, but LHCs with low a / b ratios were more positively correlated with SIR spectra. These findings indicate that the spectra of the photosynthetic pigments and constructed photosystems and antenna proteins significantly align with the terrestrial solar spectra to allow the safe and efficient use of solar radiation.